Corrupción punible y acuerdo ilícito: una aproximación a la noción del Unrechtsvereinbarung - Ambos, Kai (Estudios penales y criminologicos, 2021)
Although the identification of the concept of corruption is the basis of any reasonable anti-corruption program, it is a task that has not been achieved so far. This contribution provides an approximation to the essential characteristics of the German concept of the Unrechtsvereinbarung, which essentially refers to the idea of an illicit agreement. On this basis —and in the light of some German cases— it will be shown how that concept can limit the broad legal regulation of corruption and how useful it is for the construction of a reasonable anti-corruption agenda.